PEMUATAN KETENTUAN PIDANA DALAM PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG - Ali Marwan Hsb (Eksekusi : Journal Of Law, 2021)
Based on Article 11 Law Number 12 of 2011 on Legislation Making mentioned material contents of a Government Regulation in Lieu of Law are similar to those of a Law. This then becomes the question wheter what is meant by the material content includes material content regarding criminal provisions. In practice, after comes into force Law Number 12 of 2011 on Legislation Making, there are Government Regulation in Lieu of Law which contents criminal provisions. In this paper, it is stated that Government Regulation in Lieu of Law should not contents criminal provisions, because in addition contrary to reference techniques on Law Number 12 of 2011 on Legislation Making, loading of criminal provisions also has the potential violate human rights.